Baseline Dietary Restraint Predicts Negative Treatment Outcomes after 12 Months in Children and Adolescents with Obesity Participating in a Lifestyle Intervention - Albayrak, Özgür (Obes Facts, 2019)
OBJECTIVE: Current lifestyle interventions for children and adolescents with obesity often exclude patients with an eating pathology, leaving the impact of eating pathologies on treatment outcomes largely unconsidered. We investigated the predictive value of disordered eating symptoms on BMI z-score reduction in a sample of 111 German children and adolescents with overweight (90th percentile ≤ BMI < 97th percentile) and obesity (BMI > 97th percentile) aged 7–15 years in an outpatient lifestyle intervention program. METHODS: We defined a BMI z-score reduction of more than 5% after 12 months as a successful outcome. Disordered eating symptoms (i.e., dietary restraint, emotional eating, external eating, and binge eating) were assessed at baseline with the Eating Pattern Inventory (EPI-C) and the “bulimia” scale of the Eating Disorder Inventory (EDI-2). Covariates were: baseline z-BMI, age, gender, and maternal education level. RESULTS: Multiple regression analysis revealed that dietary restraint significantly predicted change in BMI z-scores between baseline and T1. Higher levels of dietary restraint were associated with a lower BMI z-score reduction between T0 and T1. To compare non-completers with completers on the 4 eating behavior scales, we used MANCOVA. At baseline, children who subsequently dropped out of the program prematurely showed significantly higher dietary restraint scores than children who completed the intervention, irrespectively of their gender, age, and BMI z-score at baseline and their mother's education level. DISCUSSION: Our results provide further evidence that the analysis of treatment processes in lifestyle intervention programs for children and adolescents with overweight and obesity should take into account a broader multidimensional approach including eating and dietary habits.